2021
DOI: 10.1055/s-0040-1722688
|View full text |Cite
|
Sign up to set email alerts
|

Test–Retest Reliability and Construct Validity of the German Translation of the Gait Outcome Assessment List (GOAL) Questionnaire for Children with Ambulatory Cerebral Palsy

Abstract: The Gait Outcome Assessment List (GOAL) is a patient or caregiver-reported assessment of gait-related function across different domains of the International Classification of Functioning, Disability, and Health (ICF) developed for ambulant children with cerebral palsy (CP). So far, the questionnaire is only available in English. The aim of this study was to translate the GOAL into German and to evaluate its reliability and validity by studying the association between GOAL scores and gross motor function as cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…SEMs across GMFCS levels were different for specific domains. Combined with previous relative reliability measures and validity, 13–16 these results provide a more comprehensive evaluation of the GOAL's psychometric properties, particularly the ability to discriminate true change from measurement error. This increases the confidence of clinicians in the ability of the GOAL to provide an accurate and reliable assessment rating of a child's function difficulty, pain and fatigue, and happiness with bracing and self‐esteem over time.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…SEMs across GMFCS levels were different for specific domains. Combined with previous relative reliability measures and validity, 13–16 these results provide a more comprehensive evaluation of the GOAL's psychometric properties, particularly the ability to discriminate true change from measurement error. This increases the confidence of clinicians in the ability of the GOAL to provide an accurate and reliable assessment rating of a child's function difficulty, pain and fatigue, and happiness with bracing and self‐esteem over time.…”
Section: Discussionmentioning
confidence: 77%
“…This is the first study to investigate the absolute reliability of the GOAL and adds an important dimension to the collection of studies that demonstrate its psychometric properties 13–16 . The study provides clinicians with essential information regarding the SEM and MDC necessary to interpret scores at one or more points in time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A number of studies have validated the GOAL questionnaires to date and these showed that they were able to discriminate between GMFCS levels I-III. 13,14 Moderate positive correlations were found between the GOAL scores and the walking and activities lists in the Functional Mobility Scale and Functional Assessment Questionnaire. 13 A moderate negative correlation was found between the total GOAL scores and the gait profile score derived from the three-dimensional gait analysis.…”
mentioning
confidence: 97%
“…Although the psychometric properties of GOAL's total and seven difficulty, frequency, and unhappiness domain scores have been demonstrated across multiple clinical sites, [10][11][12] very little is known about the properties of the goal prioritization items. Making sense of 49 different goals is challenging both from clinical and research perspectives and we sought to address this concern.…”
mentioning
confidence: 99%